Respuesta :
[tex] 4x^2 - 11x + 6 = 0\\
4x^2-8x-3x+6=0\\
4x(x-2)-3(x-2)=0\\
(4x-3)(x-2)=0 [/tex]
Answer: The correct option is (C) [tex](4x-3)(x-2)=0.[/tex]
Step-by-step explanation: We are given to select the correct factored form of the following quadratic equation.
[tex]4x^2-11x+6=0[/tex]
To do so, we need to factorize the left hand side of the above equation.
We have
[tex]4x^2-11x+6=0\\\\\Rightarrow 4x^2-8x-3x+6=0\\\\\Rightarrow 4x(x-2)-3(x-2)=0\\\\\Rightarrow (4x-3)(x-2)=0.[/tex]
Therefore, the correct factored form of the given equation is
[tex](4x-3)(x-2)=0.[/tex]
Thus, (C) is the correct option.